The Violence in the Name of God: Landscape of Radical Islamic Thought and Action in Indonesia (Religion, Culture, and State Journal, 2022)
The thoughts and actions of religious radicalism in Indonesia are increasingly massive and hard to prevent. The existence of this group is neatly organized with the large followers, especially among young people. Their understanding of Islam is very textual-atomistic. Theirslogan conveys the enforcement of the caliphate or the law of Allah in the totality of human life both in society and a state. The presence of this group greatly threatens the existence of ukhuwah Islamiyah and ukhuwainsaniyah. The struggle against the threat in Indonesia requires a coherent and comprehensive strategy. The better religious understanding of current religious change and thecontinuous support from all parties; in terms of religious tolerance should be encouraged to stem the songs of hard-line Islamic groups. The government must seriously increase preaching by preachers, especially those published on YouTube, and well-known writings on various sites. In addition, the government must make serious efforts continuously; to support the interfaith dialogue and increase the public awareness about the dangers of radicalism in social and state life.